The Pros and Cons of Mesenchymal Stem Cell-Based Therapies - Musiał-Wysocka, Aleksandra; Kot, Marta; Majka, Marcin (Cell transplantation, 2019)
The need to search for new, alternative treatments for various diseases has prompted scientists and physicians to focus their attention on regenerative medicine and broadly understood cell therapies. Currently, stem cells are being investigated for their potentially widespread use in therapies for many untreatable diseases. Nowadays modern treatment strategies willingly use mesenchymal stem cells (MSCs) derived from different sources. Researchers are increasingly aware of the nature of MSCs and new possibilities for their use. Due to their properties, especially their ability to self-regenerate, differentiate into several cell lineages and participate in immunomodulation, MSCs have become a promising tool in developing modern and efficient future treatment strategies. The great potential and availability of MSCs allow for their various clinical applications in the treatment of many incurable diseases. In addition to their many advantages and benefits, there are still questions about the use of MSCs. What are the mechanisms of action of MSCs? How do they reach their destination? Is the clinical use of MSCs safe? These are the main questions that arise regarding MSCs when they are considered as therapeutic tools. The diversity of MSCs, their different clinical applications, and their many traits that have not yet been thoroughly investigated are sources of discussions and controversial opinions about these cells. Here, we reviewed the current knowledge about MSCs in terms of their therapeutic potential, clinical effects and safety in clinical applications.